PEMBELAJARAN KOOPERATIF TIPE STAD MENGGUNAKAN MEDIA KARTU SOAL PADA MATERI SPLDV KELAS VIII SMP - Maria Veransiana Riwu; Gregorius Taga; Yasinta Yenita Dhiki (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
This study purpose to determine the effect of the application of cooperative learning type STAD on student mathematics learning outcomes. This type of research used an experiment with Perdiktor variable: X is the result of the students' pre-test. Response Variable: Y is the change that occurs between the pretest and posttest values. The sample consisted of 20 students of class VIII SMP Negeri 2 Ende Selatan. Based on the analysis of covariance, it shows that F (count =) 32.95 is greater than F (table =) 4.38 with dk numerator = 1 and dk denominator = 19 which gives a significant value, indicating that the STAD Type Cooperative Learning Using question card media can improving student learning outcome results for Two-Variable Linear Equation System Material in Class VIII SMP Negeri 2 Ende Selatan for academic Year 2019/2020.